THE PROFILE OF LUXURY PRODUCTS CONSUMER: THE ROMANIAN CASE - Amalia DUTU; Otilia OLTEANU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The future of the market is connected to the fast changing trends in customers profile and behaviours. Thus, luxury companies have started to be focused on a new consumer class that is rising nowadays and will be relevant within the close future. That is way; companies are strategically focused on understanding and attracting the younger segments of the population as Gen Z: the customers of the future. Any way the concept of luxury is debatable and depends on countries, social values and life style, culture factors etc. Even if the Romanian luxury market is still under development in the context of the low income of Romanian consumers in comparison to the West European citizens, there is a lot of growth potential. Thus, the aim of this research paper is to measure the Romanian consumers’ perception of luxury brands correlated to independent variables as: gender, education, monthly revenue and age and, thus, to identify a consumer typology in this respect. In order to achieve the purpose of the research study a consumer survey was conducted in Arges County. The results of the study relived the fact that luxury perception vary on a great extent due to age, education, level of income and cultural context.